Words, music and gender - Gadpaille, Michelle, 1953-; Kennedy, Victor (Cambridge Scholars Publishing, 2020)
Musicians, teachers and those who love music will find in this volume some answers to the question of how gender affects its practice, performance and reception. What was performing like for female rock singers in the 20th century? How did Bowie change our concept of performer identity? Just how sexist are the lyrics in glam metal songs? Is rap as homophobic as has been thought? Can female metal singers growl as well as men? Are LGBTQ+ issues reflected in 21st century music? Did Canadian New Wave groups tackle major social issues? How do Shakespeare and Joyce use musical puns and allusions? Fr.